THE EFFECTIVENESS AND SAFETY OF ISOMETRIC RESISTANCE TRAINING FOR ADULTS WITH RAISED BLOOD PRESSURE: A SYSTEMATIC REVIEW AND META-ANALYSIS. (April 2021) - Hansford, Harrison; Parmenter, Belinda; Wewege, Michael; Mckleod, Kelly; Smart, Neil; Schutte, Alette; Jones, Matthew
Abstract : Objective: Isometric resistance training (IRT) has demonstrated anti-hypertensive effects, but safety data is limited. Determine the effectiveness and safety of IRT compared to non-exercising control in adults with raised blood pressure. Design and method: We conducted a systematic review of published and unpublished trials up to August 2020. We included randomised control trials comparing IRT conducted for at least 3 weeks to a non-exercising, sham or lifestyle modification control in adults with raised blood pressure (systolic greater or equal to 130 and/or diastolic greater than or equal to 85mmHg). The outcomes were office, ambulatory and central blood pressure, as well as safety (adverse events). We assessed risk of bias with the Cochrane risk of bias tool and strength of evidence with GRADE. We conducted random-effects meta-analyses in R. Results: 24 trials of 1143 participants were included, mean age = 56 ± 9yrs, 56% female. IRT resulted in clinical and statistically significant reductions in both office systolic (-6.72 mmHg, 95% CI -8.64 to -4.79, p < 0.0001) and diastolic blood pressure (-3.80 mmHg, 95% CI -5.22 to -2.38, p < 0.0001) however, the results of studies differed significantly, with the overall quality being very low. IRT also resulted in clinical and statistically significant reductions in central systolic (-7.48mmHg, 95% CI -14.89 to -0.07, p = 0.035) and diastolic blood pressure (-3.75mmHg, 95% CI -6.38 to -1.12, p = 0.005), though the quality of evidence was low. 24hr ambulatory systolic (-2.77mmHg, 95% CI -6.80 to 1.25, p = 0.18) blood pressure did not see a significant reduction but diastolic blood pressure did (-2.39mmHg, 95% CI -4.28 to -0.40, p = 0.02), with very low-quality evidence. The findings of 964 participants with data for adverse events there were 8 events in the IRT group and one in the control group; equating to one adverse event per 28, 428 bouts of IRT. There were no serious adverse events. All trials were at a high risk of bias. Conclusions: IRT reduces office and central blood pressure with clinical and statistical significance although the quality of evidence is very low and low respectively. IRT appears safe with few adverse events occurring. High-quality trials are required. Figure. No caption available.